2021
DOI: 10.1186/s12935-021-02136-y
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer: epigenetics, drug resistance, and progression

Abstract: Ovarian cancer (OC) is one of the most common malignant tumors in women. OC is associated with the activation of oncogenes, the inactivation of tumor suppressor genes, and the activation of abnormal cell signaling pathways. Moreover, epigenetic processes have been found to play an important role in OC tumorigenesis. Epigenetic processes do not change DNA sequences but regulate gene expression through DNA methylation, histone modification, and non-coding RNA. This review comprehensively considers the importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 158 publications
(144 reference statements)
0
47
0
Order By: Relevance
“…Ovarian cancer is one of the most malignant and fatal gynecological tumors. High-grade serous ovarian cancer (HGSOC) is a critical histological type of ovarian cancer [ 2 , 28 , 29 ]. Germline mutations in BRCA1 and BRCA2 , which are reported in 10–15% of ovarian cancers, play an essential role as genetic risk factors for cancer development [ 30 ].…”
Section: Single-cell Sequencing-matched Cancer Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Ovarian cancer is one of the most malignant and fatal gynecological tumors. High-grade serous ovarian cancer (HGSOC) is a critical histological type of ovarian cancer [ 2 , 28 , 29 ]. Germline mutations in BRCA1 and BRCA2 , which are reported in 10–15% of ovarian cancers, play an essential role as genetic risk factors for cancer development [ 30 ].…”
Section: Single-cell Sequencing-matched Cancer Treatmentmentioning
confidence: 99%
“…In addition, BRCA1 mutations are strongly associated with poor clinical outcomes in HGSOC patients [ 31 , 32 ]. In 2011, The Cancer Genome Atlas (TCGA), using NGS and microarray data analyzed from HGSOC patients, revealed four subtypes of HGSOC based on gene expression: mesenchymal, immune response, proliferation, and differentiation [ 2 , 33 ]. Using NGS data, Murakami et al established a genetically consistent histopathological classification system for HGSOC.…”
Section: Single-cell Sequencing-matched Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to immunotherapy, checkpoint inhibitors have poor efficacy because most OCs are characterized by low levels of neoantigens on cancer cells [ 17 ]. In summary, OC is still incurable [ 17 19 ]. Therefore, a greater understanding of the signalling cascades involved in OC progression to identify markers for surveillance detection and targets for new therapies will aid in diagnosis and treatment, which are vital to clinical outcomes for OC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetics is the premise of studying heritable changes in gene expression and function that do not involve DNA sequence alterations through certain mechanisms, mainly including regulatory mechanisms such as DNA methylation, histone modi cation, and RNA editing (Tran, MacFarlane, Kong, O'Connor, & Yu, 2016).As research has progressed, it has been found that epigenetic inheritance plays an important role in the development of a variety of major diseases. In ovarian cancer, endometrial cancer, as well as cervical cancer, there have been many studies demonstrating the in uence of genetic and epigenetic modi cations on tumor initiation and progression(Efthymia Papakonstantinoua et al, 2020;Oliveira et al, 2021;Xie et al, 2021). LncRNAs are a class of RNAs with transcripts longer than 200nt that play important regulatory roles in regulating gene expression, life development and disease development, and mainly in the nucleus to regulate epigenetic modi cations (Hosono et al, 2017).In this study, we aimed to explore the signaling axis of epigenetic modi cation in serum exosomes from ovarian cancer patients and their potential therapeutic targets using whole transcriptome sequencing, TEM, and Sanger analysis.…”
Section: Introductionmentioning
confidence: 99%